Cerium as a possible stabilizer of ThMn12-type iron-based compounds: A first-principles study. (1st April 2020) - Harashima, Yosuke; Fukazawa, Taro; Miyake, Takashi
Graphical abstract: Abstract: The structural stability of CeFe12 is investigated by using first-principles calculation. The formation energies of CeFe12 relative to the Ce2 Fe17 + Fe phase and to the CeFe2 + Fe phase are calculated with the assumptions of trivalency and tetravalency for Ce. We compare them with corresponding results for Nd, Sm, and Zr. Our results suggest that the tetravalent Ce is a promising stabilizer of the ThMn12 structure. We also show that the stabilizing effect depends as much on the valency as on the size of R (rare-earth) element by investigating R Fe12 where R is assumed to have a hypothetical valency.